EFEKTIVITAS AKUN TWITER @ASUMSI SEBAGAI MEDIA PENYEBARAN INFORMASI BAGI REMAJA DESA MULIOREJO KECAMATAN SUNGGAL - Cut Luthfia Tari Efriyeni; Syahrul Abidin (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Twitter is a social media that is not only effective for communicating but also for presenting a lot of information online. An example of a twitter account that presents this information is @Asumsi ngThis account provides all kinds of information. The theory used in this study is the effectiveness of communication. The purpose of this research is to find out how effective this account is as a medium of information for youth in the Sunggal sub-district village. This study uses a qualitative approach with descriptive research methods. Data collection uses literature, books, field studies, interviews, and observations. The results of the study show that the credibility of the Twitter account @Asumsii can be trusted. In addition, the dissemination of information is fast so that the message does not seem basic and the contents of the messages are also easy to understand. In conclusion, the Twitter account @Asusi in fulfilling information needs has proven to be effective in meeting the information needs of young people in Muliorejo Village, Sunggal District.